Optical laminate, manufacturing method thereof, and smart window including the same

By directly forming a conductive layer on the polarized plate without the need for a separate substrate, the manufacturing process is simplified, the thickness of the laminate material is reduced and the light transmittance is improved, and the problems of high cost, large thickness and easy damage in the prior art are solved.

JP2025503900APending Publication Date: 2025-02-06DONGWOO FINE CHEM CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2024543196
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-01-21
Filing Date
2022-12-16
Publication Date
2025-02-06

AI Technical Summary

Technical Problem

The existing variable transmittance optical laminates include independent substrates during the manufacturing process, resulting in increased costs, increased thickness and light transmittance changes, and cracks and scratches are prone to occur.

Method used

A conductive layer is directly formed on one side of the polarized plate, an independent substrate is omitted, and a functional layer is used to increase the surface hardness, simplify the manufacturing process and reduce thickness.

Benefits of technology

The manufacturing process is simplified, the thickness of the laminate is reduced, and the light transmittance is improved, reducing the probability of cracks and scratches.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025503900000001_ABST
    Figure 2025503900000001_ABST
Patent Text Reader

Abstract

The present invention relates to a variable transmittance optical laminate, a manufacturing method thereof, and a smart window including the same, the variable transmittance optical laminate including a first polarizing plate including a first functional layer, a first transparent conductive layer formed on one side of the first polarizing plate, a second polarizing plate including a second functional layer and facing the first polarizing plate, a second transparent conductive layer formed on one side of the second polarizing plate and facing the first transparent conductive layer, and a liquid crystal layer provided between the first transparent conductive layer and the second transparent conductive layer, wherein at least one of the first transparent conductive layer and the second transparent conductive layer is formed in direct contact with one of the first polarizing plate and the second polarizing plate, and the first functional layer and the second functional layer have a surface pencil hardness of 3B to 6H.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a variable transmittance optical laminate, a method for producing the same, and a smart window including the same. [Background technology]

[0002] In general, an external light blocking coating is often applied to glass windows of vehicles and other means of transportation. However, the glass windows of conventional means of transportation have a fixed transmittance, and the external light blocking coating also has a fixed transmittance. Therefore, the windows of such conventional means of transportation have a fixed overall transmittance, which may lead to accidents. For example, if the overall transmittance is set low, there is no problem during the day when there is sufficient light in the surroundings, but there is a problem that the driver, etc., has difficulty in properly checking the surroundings of the means of transportation at night when there is insufficient light in the surroundings. Alternatively, if the overall transmittance is set high, there is a problem that the driver, etc., may be dazzled during the day when there is sufficient light in the surroundings. For this reason, a variable transmittance optical laminate capable of changing the transmittance of light when a voltage is applied has been developed.

[0003] The variable transmittance optical stack is driven by applying a voltage to drive the liquid crystal to change the transmittance. The variable transmittance optical stack developed to date is manufactured by forming a conductive layer for driving the liquid crystal on a separate substrate and combining it with other elements such as a polarizer.

[0004] For example, Japanese Patent Application Laid-Open No. 2018-010035 also discloses a variable transmittance optical laminate including a transparent electrode layer formed on a polycarbonate (PC) substrate having a predetermined thickness.

[0005] However, when a separate substrate is used to form the conductive layer, the manufacturing process becomes complicated, which increases manufacturing costs, and the thickness of the laminate increases, resulting in a phase difference and causing a change in transmittance.

[0006] In addition, if a separate substrate for forming a conductive layer is not simply included to solve the above problem, cracks may occur in components such as the conductive layer due to pressure applied by the spacer during the process, especially during the bonding process of the upper and lower plates, and chemical reactions between the liquid crystal and the alignment film.

[0007] Therefore, there is a need to develop a variable transmittance optical laminate that does not include a separate substrate for forming a conductive layer, thereby simplifying the manufacturing process and reducing the thickness, while preventing cracks or scratches that occur during the process. Summary of the Invention [Problem to be solved by the invention]

[0008] An object of the present invention is to provide a variable transmittance optical laminate that does not require a separate substrate for forming a conductive layer, and thus has a simplified manufacturing process.

[0009] Another object of the present invention is to provide a variable transmittance optical laminate that does not include a separate substrate for forming a conductive layer, and thus has a significantly reduced thickness.

[0010] Another object of the present invention is to provide a variable transmittance optical laminate having improved transmittance in a transmission mode by not including a separate substrate for forming a conductive layer.

[0011] Another object of the present invention is to provide a variable transmittance optical laminate that includes a functional layer that can improve surface hardness, thereby minimizing cracks or scratches that occur during processing.

[0012] Another object of the present invention is to provide a smart window including the variable transmittance optical laminate, and a fitting for an automobile or building to which the smart window is applied.

[0013] However, the problems to be solved by the present invention are not limited to those mentioned above, and other problems not mentioned will be clearly understood by those skilled in the art from the following description. [Means for solving the problem]

[0014] The present invention relates to a variable transmittance optical laminate comprising a first polarizing plate including a first functional layer, a first transparent conductive layer formed on one side of the first polarizing plate, a second polarizing plate including a second functional layer and facing the first polarizing plate, a second transparent conductive layer formed on one side of the second polarizing plate and facing the first transparent conductive layer, and a liquid crystal layer provided between the first transparent conductive layer and the second transparent conductive layer, wherein at least one of the first transparent conductive layer and the second transparent conductive layer is formed in direct contact with one of the first polarizing plate and the second polarizing plate, and the first functional layer and the second functional layer have a surface pencil hardness of 3B to 6H.

[0015] In the first aspect of the present invention, the first and second functional layers may have a surface pencil hardness of HB to 6H.

[0016] In a second aspect of the present invention, the first functional layer and the second functional layer may include at least one of a hard coating layer and a low refractive index layer.

[0017] In a third aspect of the present invention, the low refractive index layer may contain one or more selected from the group consisting of SiO2, Al2O3, MgF2, CaF2, and cryolite.

[0018] In a fourth aspect of the present invention, at least one of the first transparent conductive layer and the second transparent conductive layer may be formed in direct contact with either one of the first polarizing plate and the second polarizing plate without the inclusion of a separate substrate between the transparent conductive layer and either one of the first polarizing plate and the second polarizing plate.

[0019] In a fifth aspect of the present invention, at least one of the first transparent conductive layer and the second transparent conductive layer may be formed in direct contact with either one of the first polarizing plate and the second polarizing plate, including an easy-adhesion layer between the transparent conductive layer and either one of the first polarizing plate and the second polarizing plate.

[0020] In a sixth aspect of the present invention, at least one of the first transparent conductive layer and the second transparent conductive layer may contain one or more materials selected from the group consisting of transparent conductive oxides, metals, carbon-based materials, conductive polymers, conductive inks, and nanowires.

[0021] In a seventh aspect of the present invention, at least one of the first polarizing plate and the second polarizing plate may further include one or more layers selected from the group consisting of a protective layer, a retardation adjusting layer, and a refractive index adjusting layer.

[0022] In an eighth aspect of the present invention, at least one of the first polarizing plate and the second polarizing plate may have a thickness of 30 to 200 μm.

[0023] In a ninth aspect of the present invention, the liquid crystal layer may include one or more spacers selected from the group consisting of a ball spacer and a column spacer.

[0024] In a tenth aspect of the present invention, the spacer may have a diameter of 1 to 10 μm.

[0025] In an eleventh aspect of the present invention, an area of ​​the spacer in the liquid crystal layer may be 0.01% to 10% of the area of ​​the liquid crystal layer.

[0026] In a twelfth aspect of the present invention, the variable transmittance optical laminate may further include one or more layers selected from the group consisting of an alignment film, an adhesive layer, and an ultraviolet absorbing layer.

[0027] The present invention also relates to a method for producing the variable transmittance optical laminate.

[0028] The present invention also relates to a smart window comprising the variable transmittance optical laminate.

[0029] The present invention also relates to a means of transportation comprising said smart window.

[0030] The present invention also relates to an automobile in which the smart window is applied to at least one of a front window, a rear window, a side window, a sunloop window, and an interior partition.

[0031] The present invention also relates to a wearable device including the smart window.

[0032] The present invention also relates to a building fixture including the smart window. Effect of the Invention

[0033] According to the variable transmittance optical laminate of the present invention, the process of forming a conductive layer on a substrate and then bonding it to other components required for forming a conventional optical laminate can be omitted, and the manufacturing process can be simplified compared to the conventional optical laminate.

[0034] In addition, according to the variable transmittance optical laminate of the present invention, a conductive layer is formed directly on one side of a polarizing plate, and a separate substrate for forming the conductive layer is not included, so that the thickness may be significantly reduced compared to conventional optical laminates.

[0035] In addition, according to the variable transmittance optical laminate of the present invention, a conductive layer is formed directly on one side of a polarizing plate, and a separate substrate for forming the conductive layer is not included, so that the transmittance in a light transmission mode may be improved compared to conventional optical laminates.

[0036] In addition, according to the variable transmittance optical laminate according to the present invention, since it includes a functional layer capable of improving surface hardness, it is possible to minimize cracks or scratches that occur during processing compared to conventional optical laminates. [Brief description of the drawings]

[0037] [Figure 1] FIG. 1 is a diagram showing a layered structure of a variable transmittance optical layered body according to an embodiment of the present invention. [Diagram 2] FIG. 2 is a diagram illustrating a layered structure of a smart window in accordance with one or more embodiments of the present invention. [Diagram 3] FIG. 3 is a diagram illustrating a layered structure of a smart window in accordance with one or more embodiments of the present invention. [Figure 4] FIG. 4 is a diagram illustrating a layered structure of a smart window in accordance with one or more embodiments of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0038] The present invention relates to a variable transmittance optical laminate in which a conductive layer for driving liquid crystal is directly formed on one side of a polarizing plate, thereby reducing the thickness of the laminate since a separate substrate for forming the conductive layer is not required, transmittance in a light transmission mode is improved, and cracks or scratches occurring during processing can be minimized by including a functional layer that can improve surface hardness.

[0039] More specifically, the present invention relates to a variable transmittance optical laminate including a first polarizing plate including a first functional layer, a first transparent conductive layer formed on one side of the first polarizing plate, a second polarizing plate including a second functional layer and facing the first polarizing plate, a second transparent conductive layer formed on one side of the second polarizing plate and facing the first transparent conductive layer, and a liquid crystal layer provided between the first transparent conductive layer and the second transparent conductive layer, wherein at least one of the first transparent conductive layer and the second transparent conductive layer is formed in direct contact with one of the first polarizing plate and the second polarizing plate, and the first functional layer and the second functional layer have a surface pencil hardness of 3B to 6H.

[0040] The variable transmittance optical laminate of the present invention is particularly suitable for technical fields in which light transmittance can be changed by applying a voltage, and can be used, for example, in smart windows.

[0041] A smart window is an optical structure that controls the amount of light or heat passing through by changing the light transmittance according to the application of an electric signal. That is, a smart window is designed to be able to change to a transparent, opaque or translucent state according to a voltage, and is also called variable transmittance glass, light control glass or smart glass.

[0042] The smart window may be used as a partition for dividing or protecting privacy in the interior space of a vehicle or building, or as a light window placed in an opening of a building, or as a highway sign, bulletin board, odometer, clock, or advertising screen, and may be used to replace glass in vehicles such as windows or sunroofs of automobiles, buses, airplanes, ships, or trains.

[0043] The variable transmittance optical laminate of the present invention can also be used in smart windows in the various technical fields described above, but since the transparent conductive layer is directly formed on the polarizing plate, no separate substrate is required for forming the conductive layer, and therefore the thickness is thin and the bending characteristics are advantageous, and the variable transmittance optical laminate of the present invention can be particularly preferably used in smart windows for vehicles or buildings. In one or more embodiments, the smart window to which the variable transmittance optical laminate of the present invention is applied can be used as a front window, rear window, side window, and sunroof window of an automobile, or a building fixture, and can be used for dividing the interior space of an automobile or building, such as an interior partition, or for privacy protection, in addition to blocking external light, and can also be used in wearable devices such as helmets, glasses, or watches.

[0044] Hereinafter, the embodiments of the present invention will be described in more detail with reference to the drawings. However, the following drawings attached to this specification are intended to illustrate preferred embodiments of the present invention and to facilitate a better understanding of the technical concept of the present invention together with the above-mentioned content of the invention, and therefore the present invention should not be interpreted as being limited only to the matters described in these drawings.

[0045] The terms used in this specification are for the purpose of explaining the embodiments and are not intended to limit the present invention. In this specification, the singular form includes the plural form unless otherwise specified in the text. For example, the "polarizing plate" used in this specification may mean at least one polarizing plate of the first polarizing plate and the second polarizing plate, the "transparent conductive layer" may mean at least one transparent conductive layer of the first transparent conductive layer and the second transparent conductive layer, and the "functional layer" may mean at least one functional layer of the first functional layer and the second functional layer.

[0046] As used herein, "comprises" and / or "comprising" are used in a sense that does not exclude the presence or addition of one or more other components, steps, operations and / or elements other than the stated components, steps, operations and / or elements. The same reference numerals refer to the same components throughout the specification.

[0047] Spatially relative terms such as "below," "bottom," "lower," "upper," "top," and the like, may be used to easily describe the relationship of one element or component to another element or component as depicted in the drawings. Spatially relative terms should be understood to include different orientations of elements in use or operation in addition to the orientation depicted in the drawings. For example, if an element depicted in the drawings is turned upside down, an element described as "below" or "below" another element may be placed "above" the other element. Thus, the exemplary term "below" can include both an orientation of below and above. Elements may be oriented in other directions, and thus the spatially relative terms may be interpreted accordingly.

[0048] As used herein, the "planar direction" can be interpreted as the direction perpendicular to the polarizer and / or transparent conductive layer, ie, the direction viewed from the user's viewing side.

[0049] FIG. 1 is a diagram showing a schematic diagram of a layered structure of a variable transmittance optical laminate according to one embodiment of the present invention, and FIGS. 2 to 4 are diagrams for explaining the layered structure of a variable transmittance optical laminate according to one embodiment of the present invention.

[0050] Referring to FIG. 1, a variable transmittance optical stack according to one embodiment of the present invention may include a first polarizer 100-1, a second polarizer 100-2, a first transparent conductive layer 200-1, a second transparent conductive layer 200-2, and a liquid crystal layer 300.

[0051] The polarizing plate 100 includes a polarizer 110 and at least one functional layer 120 for improving the surface hardness of the polarizing plate, and in one or more embodiments, may further include a protective layer, a retardation control layer, and a refractive index control layer.

[0052] The polarizer 110 may be any conventional or later developed polarizer, such as a stretched type polarizer or a coated type polarizer.

[0053] In one embodiment, the stretched polarizer may include a stretched polyvinyl alcohol (PVA)-based resin. The polyvinyl alcohol (PVA)-based resin may be a polyvinyl alcohol-based resin obtained by saponifying a polyvinyl acetate-based resin. Examples of polyvinyl acetate-based resins include polyvinyl acetate, which is a homopolymer of vinyl acetate, and copolymers of vinyl acetate and other monomers copolymerizable therewith. The other monomers may be unsaturated carboxylic acid-based, unsaturated sulfonic acid-based, olefin-based, vinyl ether-based, and acrylamide-based monomers having an ammonium group. The polyvinyl alcohol (PVA)-based resin may be modified, for example, polyvinyl formal or polyvinyl acetal modified with aldehydes.

[0054] In an embodiment, the coating type polarizer may be formed by a liquid crystal coating composition, which may include a reactive liquid crystal compound and a dichroic dye.

[0055] The reactive liquid crystal compound may refer to a compound that includes, for example, a mesogen skeleton and further includes one or more polymerizable functional groups. Such reactive liquid crystal compounds are variously known under the name of RM (Reactive Mesogen). The reactive liquid crystal compound can be polymerized by light or heat to form a cured film in which a polymer network is formed while maintaining the liquid crystal alignment.

[0056] The reactive liquid crystal compound may be a monofunctional or polyfunctional reactive liquid crystal compound. The monofunctional reactive liquid crystal compound is a compound having one polymerizable functional group, and the polyfunctional reactive liquid crystal compound is a compound having two or more polymerizable functional groups.

[0057] The dichroic dye is a component contained in the liquid crystal coating composition that imparts polarization properties, and has a property that the absorbance in the long axis direction of the molecule is different from that in the short axis direction. The dichroic dye may be a dichroic dye that has been used or will be developed in the future, and may include at least one selected from the group consisting of azo dyes, anthraquinone dyes, perylene dyes, merocyanine dyes, azomethine dyes, phthaloperylene dyes, indigo dyes, dioxazine dyes, polythiophene dyes, and phenoxazine dyes.

[0058] The liquid crystal coating composition may further include a solvent capable of dissolving the reactive liquid crystal compound and the dichroic dye, such as propylene glycol monomethyl ether acetate (PGMEA), methyl ethyl ketone (MEK), xylene, chloroform, etc. The liquid crystal coating composition may further include a labeling agent, a polymerization initiator, etc., within a range that does not impair the polarization properties of the coating film.

[0059] The functional layer 120 is provided to improve the hardness of the polarizing plate 100, and is not particularly limited as long as it can improve the hardness of the polarizing plate, and may include, for example, a hard coating layer and / or a low refractive index layer.

[0060] The hard coating layer may be a conventional or later developed hard coating layer, and may be formed from a composition for forming a hard coating layer, including, for example, an acrylate or epoxy compound, inorganic fine particles, and / or a photoinitiator. The acrylate compound may include a monomer or oligomer containing a (meth)acrylate group, and the term "(meth)acryl-" as used herein is used to mean "methacryl-", "acryl-", or both. Non-limiting examples of the acrylate compound include neopentyl glycol acrylate, 1,6-hexanediol (meth)acrylate, propylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, dipropylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, trimethylolethane tri(meth)acrylate, 1,2,4-cyclohexane tetra(meth)acrylate, pentaglycerol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, pentaerythritol tri(meth)acrylate, and dipentaerythritol tri(meth)acrylate. Examples of the acrylates include 2-hydroxyethyl isocyanurate, dipentaerythritol penta(meth)acrylate, dipentaerythritol tetra(meth)acrylate, dipentaerythritol hexa(meth)acrylate, tripentaerythritol tri(meth)acrylate, tripentaerythritol hexatri(meth)acrylate, bis(2-hydroxyethyl)isocyanurate di(meth)acrylate, hydroxyethyl(meth)acrylate, hydroxypropyl(meth)acrylate, hydroxybutyl(meth)acrylate, isooctyl(meth)acrylate, iso-dexyl(meth)acrylate, stearyl(meth)acrylate, tetrahydrofurfuryl(meth)acrylate, phenoxyethyl(meth)acrylate, and isoborneol(meth)acrylate. These may be used alone or in combination of two or more.The acrylate compound may include an epoxy (meth)acrylate compound and / or a urethane (meth)acrylate compound. The epoxy compound may include a monomer or oligomer having at least one epoxy group in the molecule. The epoxy group may be an alicyclic epoxy group. The alicyclic ring included in the epoxy group may have 3 to 7 carbon atoms, for example, an alicyclic epoxy group (cyclohexyl epoxy) containing a cyclohexane ring. The alicyclic ring may have a substituent. For example, the alicyclic ring may include an alkyl substituent having 1 to 20 carbon atoms. If the alkyl substituent has more than 20 carbon atoms, it may be disadvantageous in terms of curing speed. The alkyl substituent may be a straight-chain type or a branched type, and if it is a branched type, the number of carbon atoms may be 3 or more.

[0061] According to an embodiment of the present invention, the composition for forming a hard coating layer includes inorganic fine particles. According to an embodiment of the present invention, the inorganic fine particles may be inorganic fine particles having a nano-scale particle size, for example, nano-particles having a particle size of 100 nm or less, or 10 to 100 nm, or 10 to 50 nm. Furthermore, the inorganic fine particles may be, for example, silica fine particles, aluminum oxide particles, titanium oxide particles, or zinc oxide particles. By including the inorganic fine particles, the hardness of the hard coating layer can be further improved. According to an embodiment of the present invention, the inorganic fine particles may be included in an amount of 10 to 60 parts by weight, or 20 to 50 parts by weight, based on 100 parts by weight of the composition for forming a hard coating layer. By including the inorganic fine particles in the above range, the hardness of the hard coating layer can be improved by adding the inorganic fine particles within a range that does not deteriorate the physical properties of the composition for forming a hard coating layer.

[0062] According to an embodiment of the present invention, the composition for forming a hard coating layer includes a photoinitiator, which may be, but is not limited to, 1-hydroxy-cyclohexyl-phenyl ketone, 2-hydroxy-2-methyl-1-phenyl-1-propanone, 2-hydroxy-1-[4-(2-hydroxyethoxy)phenyl]-2-methyl-1-propanone, methylbenzoyl formate, α,α-dimethoxy-α-phenylacetophenone, 2-benzoyl-2-(dimethylamino-)-1-[4-(4-morpholinyl)phenyl]-1-butanone, 2-methyl-1-[4-(methylthio)phenyl]-2-(4-morpholinyl)-1-propanone diphenyl(2,4,6-trimethylbenzoyl)-phosphine oxide, or bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide. In addition, examples of products currently available on the market include Irgacure 184, Irgacure 500, Irgacure 651, Irgacure 369, Irgacure 907, Darocur 1173, Darocur MBF, Irgacure 819, Darocur TPO, Irgacure 907, Esacure KIP 100F, etc. These photoinitiators may be used alone or in combination of two or more different types.

[0063] According to an embodiment of the present invention, the photoinitiator may be included in an amount of 0.5 to 10 parts by weight, preferably 1 to 5 parts by weight, based on 100 parts by weight of the composition for forming a hard coating layer. When the photoinitiator is in the above range, sufficient crosslinking photopolymerization can be achieved without deteriorating the physical properties of the hard coating layer.

[0064] Meanwhile, the composition for forming a hard coating layer may further include additives commonly used in the technical field to which the present invention belongs, such as a surfactant, an anti-yellowing agent, a leveling agent, an antifouling agent, etc. In addition, the content of the additives is not particularly limited since it can be variously adjusted within a range that does not deteriorate the physical properties of the composition for forming a hard coating layer according to the present invention.

[0065] The low refractive index layer may be provided to improve the hardness of the polarizing plate within the scope of the present invention. The low refractive index layer may contain one or more low refractive index agents selected from the group consisting of SiO2, Al2O3, MgF2, CaF, and cryloite, and in some embodiments, may contain the compound or resin used in the hard coating layer. The hard coating layer and the low refractive index layer may be used alone, or in some embodiments, may be used as a multi-layer structure.

[0066] The functional layer 120 may be formed on one surface of the polarizer 110 in direct contact therewith as shown in Fig. 1, but is not limited thereto. For example, when the polarizing plate includes a retardation control layer or a refractive index control layer, the functional layer 120 may be formed on one surface of the retardation control layer or the refractive index control layer, and the functional layer, the retardation control layer, the refractive index control layer, and the polarizer may be sequentially laminated.

[0067] The functional layer 120 is preferably formed on the liquid crystal layer 300 side of the polarizer 110, i.e., on the inner side of the polarizer 110. For example, the first functional layer 120-1 and the second functional layer 120-2 may be provided on the inner sides of the first polarizer 110-1 and the second polarizer 110-2, respectively, and arranged to face each other. In this case, the functional layer has an advantage of minimizing cracks or scratches that occur during the manufacturing or processing process of the optical laminate by imparting a level of hardness suitable for forming members such as a transparent conductive layer to the polarizer.

[0068] The functional layer 120 may preferably have a surface pencil hardness of 3B to 6H, more preferably HB to 6H. The surface pencil hardness may be measured by applying a load of 500 g using a pencil hardness tester (manufactured by SUKBO Chemical Co., Ltd., Korea) to measure the pencil hardness of the functional layer, and may be evaluated by applying 5 times per pencil hardness using a Mitsubishi product, heat treating at 100° C. for 10 minutes, and determining whether scratches are visually confirmed. When the surface pencil hardness of the functional layer satisfies the above range, it may not only have excellent abrasion resistance, but also further improve the bending resistance or durability of the optical laminate.

[0069] In one or more embodiments, the first functional layer 120-1 and the second functional layer 120-2 may each have a thickness of 1 to 30 μm, and more preferably, 2 to 20 μm. The thickness may refer to the thickness after drying, and when the thickness of the first functional layer 120-1 and the second functional layer 120-2 satisfies the above range, the functional layer 120-1 and the second functional layer 120-2 may have excellent hardness, may be thin, and may have improved bending resistance and durability.

[0070] The protective layer serves to preserve the polarization characteristics of the polarizer from post-processing and external environments, and may be implemented in the form of a protective film.

[0071] The protective layer may be formed on one or both sides of the polarizer in direct contact therewith, but is not limited thereto. For example, the protective layer may be used as a multi-layer structure in which one or more protective layers are continuously stacked, or may be formed on another member such as a retardation adjusting layer in direct contact therewith.

[0072] In one or more embodiments, the protective layer may include one or more selected from the group consisting of polyethylene terephthalate (PET), polyethylene isophthalate (PEI), polyethylene naphthalate (PEN), polybutylene terephthalate (PBT), diacetyl cellulose, triacetyl cellulose (TAC), polycarbonate (PC), polyethylene (PE), polypropylene (PP), polymethyl acrylate (PMA), polymethyl methacrylate (PMMA), polyethyl acrylate (PEA), polyethyl methacrylate (PEMA), and cyclic olefin polymer (COP).

[0073] The retardation control layer is for complementing the optical properties of the optical laminate and may be implemented in the form of a retardation film, etc., or may be a conventional or later developed retardation film, etc. For example, a quarter wave plate (1 / 4 wave plate) or a half wave plate (1 / 2 wave plate) for delaying the phase of light may be used, and these may be used alone or in combination.

[0074] The retardation control layer may be formed on one surface of the polarizer in direct contact therewith, but is not limited thereto. For example, the retardation control layer may be formed on one surface of the protective layer in direct contact therewith, or may be formed on one surface of the refractive index control layer in direct contact therewith.

[0075] The retardation control layer may be a polymer stretched film obtained by stretching a polymer film capable of imparting optical anisotropy by stretching in an appropriate manner, or a liquid crystal polymer film.

[0076] In one embodiment, the polymer stretched film may be a polymer layer including polyolefins such as polyethylene (PE) or polypropylene (PP), cycloolefin polymers (COP) such as polynorbornene, polyesters such as polyvinyl chloride (PVC), polyacrylonitrile (PAN), polysulfone (PSU), acrylic resins, polycarbonate (PC), and polyethylene terephthalate (PET), polyacrylate, cellulose ester polymers such as polyvinyl alcohol (PVA) or triacetyl cellulose (TAC), or copolymers of two or more monomers among the monomers forming the polymer.

[0077] The method for obtaining the polymer stretched film is not particularly limited, and for example, the polymer material is molded into a film and then stretched. The method for forming the film is not particularly limited, and the film can be molded into a film by known methods such as injection molding, sheet molding, blow molding, injection blow molding, inflation molding, extrusion molding, foam molding, and cast molding, and secondary processing molding methods such as compressed air molding and vacuum molding may also be used. Among them, extrusion molding and cast molding are preferably used. At this time, for example, an extruder equipped with a T-die, a circular die, or the like can be used to extrude the unstretched film. When obtaining a molded product by extrusion molding, a material in which various resin components, additives, etc. are melt-kneaded in advance can be used, or the product can be molded through melt-kneading during extrusion molding. In addition, various resin components can be dissolved using a solvent common to various resin components, such as chloroform or methylene dichloride, and then cast-dried and solidified to cast-mold the unstretched film.

[0078] The polymer stretched film may be produced by uniaxially stretching the formed film in the mechanical direction (MD, lengthwise or longitudinal direction) or uniaxially stretching the formed film in the transverse direction (TD, widthwise or transverse direction) of the mechanical direction. Also, a biaxially stretched film may be produced by stretching the formed film by a sequential biaxial stretching method of roll stretching and tenter stretching, a simultaneous biaxial stretching method by tenter stretching, a biaxial stretching method by tubular stretching, or the like.

[0079] The liquid crystal polymer film may include a reactive liquid crystal compound in a polymerized state. The reactive liquid crystal compound may be the same as that of the coating type polarizer.

[0080] In one or more embodiments, the thickness of the retardation control layer may be 10 to 100 μm in the case of a polymer stretched film, and 0.1 to 5 μm in the case of a liquid crystal polymer film.

[0081] The refractive index adjustment layer is provided to compensate for the refractive index difference of the optical laminate caused by the transparent conductive layer 200, and may serve to improve visibility by reducing the refractive index difference. The refractive index adjustment layer may also be provided to correct a hue caused by the transparent conductive layer 200. Meanwhile, when the transparent conductive layer has a pattern, the refractive index adjustment layer can compensate for the transmittance difference between a patterned region where the pattern is formed and a non-patterned region where the pattern is not formed.

[0082] Specifically, the transparent conductive layer 200 is stacked adjacent to another member (e.g., a polarizer) having a different refractive index, and a difference in light transmittance may be induced due to the difference in refractive index between the adjacent layers. In particular, when a pattern is formed on the transparent conductive layer, a problem may occur in which the patterned region and the non-patterned region are visually distinguishable. Therefore, by including the refractive index control layer, the refractive index is compensated for, thereby reducing the difference in light transmittance of the optical laminate, and in particular, when a pattern is formed on the transparent conductive layer, the patterned region and the non-patterned region are visually distinguishable.

[0083] In one embodiment, the refractive index of the refractive index adjusting layer may be appropriately selected according to the material of the adjacent other member, and may be preferably 1.4 to 2.6, and more preferably 1.4 to 2.4. In this case, light loss due to a sharp difference in refractive index between the other member and the transparent conductive layer 200 can be prevented.

[0084] The refractive index adjustment layer is not particularly limited as long as it can prevent a sharp refractive index difference between other components such as a polarizer and the transparent conductive layer 200. A compound used in forming a conventional or later developed refractive index adjustment layer may be used, and for example, the refractive index adjustment layer may be formed from a refractive index adjustment layer forming composition containing a polymerizable isocyanurate compound.

[0085] In one embodiment, the polarizing plate 100 may further include other components to supplement or enhance the properties of the polarizer in addition to the above-mentioned components, for example, an overcoat layer to further improve mechanical durability.

[0086] In one or more embodiments, the polarizing plate 100 may have a thickness of 30 to 200 μm, preferably 30 to 170 μm, and more preferably 50 to 150 μm, so that the polarizing plate 100 can be used to manufacture an optical laminate having a small thickness while maintaining optical properties.

[0087] The transparent conductive layer 200 is provided for driving the liquid crystal layer 300, and may be formed in direct contact with the polarizer 100. For example, as shown in Fig. 1, a first transparent conductive layer 200-1 and a second transparent conductive layer 200-2 may be formed in direct contact with a first polarizer 100-1 and a second polarizer 100-2, respectively.

[0088] Conventional optical laminates used in the manufacture of smart windows, etc., are manufactured by forming a conductive layer for driving liquid crystal on one side of a substrate and bonding the other side of the substrate to a polarizing plate. However, the variable transmittance optical laminate according to the present invention is characterized in that it does not include a separate substrate for forming a conductive layer, but directly forms a conductive layer on one side of a polarizing plate, thereby reducing the thickness of the laminate and improving the transmittance and bending characteristics in a light transmission mode.

[0089] In one embodiment, the transparent conductive layer 200 may be formed by direct deposition on one surface of the polarizer 100. In this case, the transparent conductive layer 200 may be formed by directly contacting the pre-treated surface of the polarizer 100 after performing a pre-treatment such as a corona treatment or a plasma treatment on one surface of the polarizer 100 in order to improve adhesion to the polarizer 100. The pre-treatment is not limited to a corona treatment or a plasma treatment, and any conventional or later developed pre-treatment process may be used within the scope of the present invention.

[0090] In another embodiment, the transparent conductive layer 200 may be formed in direct contact with the polarizer 100 via an easy-adhesion layer (not shown) provided on one side of the polarizer 100 in order to improve adhesion to the polarizer 100.

[0091] The transparent conductive layer 200 preferably has a visible light transmittance of 50% or more, and may include, for example, one or more selected from the group consisting of transparent conductive oxides, metals, carbon-based materials, conductive polymers, conductive inks, and nanowires, but is not limited thereto, and any conventional or later developed transparent conductive layer material may be used.

[0092] In one or more embodiments, the transparent conductive oxide may include one or more selected from the group consisting of indium tin oxide (ITO), indium zinc oxide (IZO), indium zinc tin oxide (IZTO), aluminum zinc oxide (AZO), gallium zinc oxide (GZO), florin tin oxide (FTO), zinc oxide (ZnO), etc. The metal may include one or more selected from the group consisting of gold (Au), silver (Ag), copper (Cu), aluminum (Al), platinum (Pt), palladium (Pd), chromium (Cr), titanium (Ti), tungsten (W), niobium (Nb), tantalum (Ta), vanadium (V), iron (Fe), manganese (Mn), cobalt (Co), nickel (Ni), zinc (Zn), and alloys containing at least one of these, for example, a silver-palladium-copper (APC) alloy or a copper-calcium (CuCa) alloy. The carbon-based material may include at least one selected from the group consisting of carbon nanotubes (CNTs) and graphene, and the conductive polymer may include at least one selected from the group consisting of polypyrrole, polythiophene, polyacetylene, PEDOT, and polyaniline. The conductive ink may be an ink in which a metal powder and a curable polymer binder are mixed, and the nanowire may be, for example, a silver nanowire (AgNW).

[0093] The transparent conductive layer 200 may also be formed in a two-layer structure by combining the above materials, for example, in a two-layer structure including a metal layer and a transparent conductive oxide layer to reduce the reflectance and increase the transmittance of incident light.

[0094] The transparent conductive layer 200 may be formed by a method commonly used in the art, for example, a coating process such as spin coating, roller coating, bar coating, dip coating, gravure coating, curtain coating, die coating, spray coating, doctor coating, kneader coating, etc.; a printing process such as screen printing, spray printing, inkjet printing, relief printing, intaglio printing, and planographic printing, etc.; and a deposition process such as CVD (chemical vapor deposition), PVD (physical vapor deposition), and PECVD (plasma enhanced chemical vapor deposition), etc.

[0095] The liquid crystal layer 300 can change the driving mode of the optical stack by controlling the transmittance of light incident from one or more directions by an electric field.

[0096] The liquid crystal layer 300 may include a liquid crystal compound and may be located, for example, in a space provided by a sealant 500 and a spacer (not shown) provided between the first polarizer 100-1 and the second polarizer 100-2 in the light control region.

[0097] The liquid crystal compound is not particularly limited as long as it is driven by an electric field and can control the light transmittance, and any conventional or later developed liquid crystal compound may be used. For example, the contents regarding the reactive liquid crystal compound of the coating type polarizer described above may be similarly applied.

[0098] The liquid crystal behavior mode of the liquid crystal layer 300 is not particularly limited, and may be driven in, for example, TN (Twisted nematic) mode as shown in FIG. 1, or may be driven in STN (Super twisted nematic) mode, VA (Vertical alignment) mode, etc.

[0099] The sealant may include a curable resin as a base resin. The base resin may be a UV-curable resin or a thermosetting resin known in the art to be used for sealants. The UV-curable resin may be a polymer of a UV-curable monomer. The thermosetting resin may be a polymer of a thermosetting monomer.

[0100] The base resin of the sealant 500 may be, for example, an acrylate-based resin, an epoxy-based resin, a urethane-based resin, a phenol-based resin, or a mixture of the above resins. In one embodiment, the base resin may be an acrylate-based resin, and the acrylate-based resin may be a polymer of an acrylic monomer. The acrylic monomer may be, for example, a polyfunctional acrylate. In another embodiment, the sealant may further include a monomer component in the base resin. The monomer component may be, for example, a monofunctional acrylate. In this specification, a monofunctional acrylate may mean a compound having one acrylic group, and a polyfunctional acrylate may mean a compound having two or more acrylic groups. The curable resin may be cured by irradiation with ultraviolet light and / or heating. The ultraviolet irradiation conditions or heating conditions may be appropriately performed within a range that does not impair the purpose of the present application. The sealant may further include an initiator, for example, a photoinitiator or a thermal initiator, as necessary.

[0101] The sealant 500 may be formed by a method commonly used in the art, for example, by drawing the sealant onto the outer periphery (i.e., non-active area) of the liquid crystal layer using a dispenser equipped with a nozzle.

[0102] The spacer may include at least one of a ball spacer and a column spacer, and is preferably a ball spacer. The number of ball spacers may be one or more, and the ball spacer preferably has a diameter of 1 to 10 μm. In addition, when viewed in a planar direction, the area of ​​the ball spacer in the liquid crystal layer 300 is preferably 0.01 to 10% of the area of ​​the liquid crystal layer 300 in terms of improving the user's visibility and the transmittance in the light-transmitting mode.

[0103] In one embodiment, the liquid crystal layer 300 may further include an alignment film 400, if necessary, which may be formed on both sides of the liquid crystal layer 300 containing a liquid crystal compound.

[0104] The alignment film 400 is not particularly limited as long as it is capable of imparting alignment to the liquid crystal compound, and may preferably include a photoalignable or photocurable polymer. For example, the alignment film 400 may be manufactured by applying and curing an alignment film coating composition including a photoalignable or photocurable polymer, a photopolymerization initiator, and a solvent.

[0105] The photo-alignable or photo-curable polymer is not particularly limited, and may be a cinnamate-based polymer, a polyimide-based polymer, or the like, such as poly(vinyl cinnamate) (PVCi), poly(siloxane cinnamate) (PSCN), poly(ω(4-chalconyloxy)alkoxyphenylmaleimide, 6-FDA-HAB-Cl, or the like. Conventional or later-developed polymers capable of exhibiting alignment may also be used.

[0106] The variable transmittance optical laminate of the present invention may further include other components within the scope of the present invention, for example, may further include an adhesive layer 600 (see Figures 2 to 4), or may further include an ultraviolet absorbing layer, etc.

[0107] The adhesive layer 600 may be formed using an adhesive or pressure-sensitive adhesive, and preferably has an appropriate adhesive strength so as to prevent peeling, air bubbles, etc. from occurring when the optical laminate is handled, as well as transparency and thermal stability.

[0108] The adhesive may be any conventional or later developed adhesive, for example a light curable adhesive.

[0109] The photocurable adhesive exhibits strong adhesive strength by being crosslinked and cured when exposed to active energy rays such as ultraviolet (UV) rays and electron beams (EB), and may be composed of reactive oligomers, reactive monomers, photopolymerization initiators, etc.

[0110] The reactive oligomer is an important component that determines the properties of the adhesive, and forms a polymer bond by photopolymerization to form a hardened coating. Usable reactive oligomers include polyester resins, polyether resins, polyurethane resins, epoxy resins, polyacrylic resins, silicone resins, etc.

[0111] The reactive monomer functions as a crosslinking agent and a diluent for the reactive oligomer, and affects the adhesive properties. Usable reactive monomers include monofunctional monomers, polyfunctional monomers, epoxy monomers, vinyl ethers, cyclic ethers, and the like.

[0112] The photopolymerization initiator absorbs light energy to generate radicals or cations to initiate photopolymerization, and may be selected from those suitable for the photopolymerizable resin.

[0113] The adhesive may be a conventional or later developed adhesive, and in one or more embodiments, may be an acrylic adhesive, a rubber adhesive, a silicone adhesive, a urethane adhesive, a polyvinyl alcohol adhesive, a polyvinylpyrrolidone adhesive, a polyacrylamide adhesive, a cellulose adhesive, a vinyl alkyl ether adhesive, etc. The adhesive is not particularly limited as long as it has adhesive strength and viscoelasticity, but in terms of availability, etc., it may be preferably an acrylic adhesive, and may contain, for example, a (meth)acrylate copolymer, a crosslinking agent, and a solvent.

[0114] The crosslinking agent may be a conventional or later developed crosslinking agent, and may include, for example, a polyisocyanate compound, an epoxy resin, a melamine resin, a urea resin, a dialdehyde, a methylol polymer, or the like, and preferably includes a polyisocyanate compound.

[0115] The solvent may include a typical solvent used in the field of resin compositions, such as alcohol compounds such as methanol, ethanol, isopropanol, butanol, and propylene glycol methoxy alcohol; ketone compounds such as methyl ethyl ketone, methyl butyl ketone, methyl isobutyl ketone, diethyl ketone, and dipropyl ketone; acetate compounds such as methyl acetate, ethyl acetate, butyl acetate, and propylene glycol methoxy acetate; cellosolve compounds such as methyl cellosolve, ethyl cellosolve, and propyl cellosolve; and hydrocarbon compounds such as hexane, heptane, benzene, toluene, and xylene. These may be used alone or in combination of two or more.

[0116] The thickness of the adhesive layer 600 may be appropriately determined depending on the type of resin acting as an adhesive, adhesive strength, the environment in which the adhesive is used, etc. In one embodiment, the adhesive layer may have a thickness of 0.01 to 50 μm, preferably 0.05 to 20 μm, and more preferably 0.1 to 10 μm, in order to ensure sufficient adhesive strength and minimize the thickness of the optical laminate.

[0117] In an embodiment, the adhesive layer 600 may be formed on one or both sides of the polarizing plate by a lamination method.

[0118] The ultraviolet absorbing layer is not particularly limited as long as it is used to prevent deterioration of the optical laminate due to ultraviolet rays. For example, it may be a salicylic acid-based ultraviolet absorber (phenyl salicylate, p-tert-butyl salicylate, etc.), a benzophenone-based ultraviolet absorber (2,4-dihydroxybenzophenone, 2,2'-dihydroxy-4,4'-dimethoxybenzophenone, etc.), a benzotriazole-based ultraviolet absorber (2-(2'-hydroxy-5'-methylphenyl)benzotriazole, 2-(2'-hydroxy-3',5'-di-t 2-(2'-hydroxy-3'-tert-butyl-5'-methylphenyl)benzotriazole, 2-(2'-hydroxy-3',5'-di-tert-butylphenyl)-5-chlorobenzotriazole, 2-(2'-hydroxy-3'-(3'',4'',5'',6''-tetrahydrophthalimidomethyl)-5'-methylphenyl)benzotriazole, 2,2-methylenebis(4-(1,1,3,3-tetramethylbutyl)-6-(2H-benzotriazo 2-(2'-hydroxy-3'-tert-butyl-5'-methylphenyl)-5-chlorobenzotriazole, 2-(2'-hydroxy-3'-tert-butyl-5'-(2-octyloxycarbonylethyl)-phenyl)-5-chlorobenzotriazole, 2-(2'-hydroxy-3'-(1-methyl-1-phenylethyl)-5'-(1,1,3,3-tetramethylbutyl)-phenyl)benzotriazole, 2-(2H-benzotriazol-2-yl)-6-(linear and side chain dodecyl)-4-methylphenol, a mixture of octyl-3-[3-tert-butyl-4-hydroxy-5-(chloro-2H-benzotriazol-2-yl)phenyl]propionate and 2-ethylhexyl-3-[3-tert-butyl-4-hydroxy-5-(5-chloro-2H-benzotriazol-2-yl)phenyl]propionate, etc.), cyanoacrylate-based ultraviolet absorbers (2'-ethylhexyl-2-cyano-3,3-diphenylacrylate, ethyl-2-cyano-3-(3',4'-methylenedioxyphenyl)-acrylate, triazine-based ultraviolet absorbers, etc. may be used, and benzotriazole-based ultraviolet absorbers and triazine-based ultraviolet absorbers, which are highly transparent and have an excellent effect of preventing deterioration of the polarizing plate and the transmittance variable layer, are preferred, and benzotriazole-based ultraviolet absorbers with a more suitable spectral absorption spectrum are particularly preferred. The benzotriazole-based ultraviolet absorbers may be bis(Bis)-modified, for example, 6,6'-methylenebis(2-(2H-benzo[d][1,2,3]triazol-2-yl)-4-(2,4,4-trimethylpentan-2-yl)phenol), 6,6'-methylenebis(2-(2H-benzo[d][1,2,3]triazol-2-yl)-4-(2-hydroxyethyl)phenol), etc.,

[0119] The present invention includes the variable transmittance optical laminate, as well as a smart window including the same. The present invention also includes an automobile in which the smart window is applied to at least one of a front window, a rear window, a side window, a sunroof window, and an interior partition, and a building fixture including the smart window.

[0120] For example, the automobile including the smart window of the present invention may be manufactured by bonding car glass 700 onto both sides of an optical laminate including a polarizing plate 100, a transparent conductive layer 200, a liquid crystal layer 300, an alignment film 400, a sealant 500, and a tacky adhesive layer 600 (see FIG. 2). For example, the automobile may be manufactured by placing an adhesive film and car glass on both sides of the optical laminate, and then heating the optical laminate at a temperature of 90° C. and a vacuum state of about 1 bar for 10 to 20 minutes using a press machine. The adhesive film may include an EVA film, a PVB film, etc.

[0121] In addition, the optical laminate may have building fixtures (glass for fixtures) 800 bonded to both sides (see FIG. 3) or one side (see FIG. 4) of it, or the optical laminate may have fixture glass coated with a UV adhesive bonded to both sides of the optical laminate and then UV cured to produce a smart window product for fixtures having the same configuration as that shown in FIG. 3, or the optical laminate may have fixture glass bonded to one side of the optical laminate using a lamination method to produce a smart window product for fixtures having the same configuration as that shown in FIG. 4. EXAMPLES

[0122] Hereinafter, the present invention will be described in detail with reference to the embodiments. However, the present invention is not limited to the embodiments disclosed below, and may be embodied in various different forms. However, the embodiments are provided to fully disclose the present invention and to fully inform those skilled in the art of the present invention of the scope of the invention, and the present invention is defined only by the scope of the claims.

[0123] Manufacturing example: Polarizing plate production (1) Swelling treatment process A 60 μm thick polyvinyl alcohol film (raw film) (manufactured by Kuraray Co., Ltd., product name "Kuraray Poval Film VF-PE#6000", average polymerization degree 2400, saponification degree 99.9 mol%) was continuously unwound from a raw roll and transported, and immersed in a swelling bath containing pure water at 20°C for 30 seconds. In this swelling process, inter-roll stretching (longitudinal uniaxial stretching) was performed with a difference in peripheral speed between the nip rolls. The stretching ratio based on the raw film was 2.5 times.

[0124] (2) Dyeing process Next, the film that had passed through the nip rolls was immersed in a dye bath at 30° C. with a mass ratio of pure water / potassium iodide / iodine / boric acid of 100 / 2 / 0.01 / 0.3 for 120 seconds. In this dyeing treatment, roll-to-roll stretching (longitudinal uniaxial stretching) was also performed with a difference in peripheral speed between the nip rolls. The stretching ratio was 1.1 times based on the film after the swelling treatment step.

[0125] (3) Crosslinking process Next, the film that had passed through the nip roll was immersed in a first crosslinking bath at 56° C., in which the mass ratio of pure water / potassium iodide / boric acid was 100 / 12 / 4, for 70 seconds. Roll-to-roll stretching (longitudinal uniaxial stretching) was performed with a difference in peripheral speed between the nip roll and a nip roll provided between the first crosslinking bath and the second crosslinking bath. The stretching ratio was 1.9 times based on the film after the dyeing process.

[0126] (4) Complementary color processing process Next, the film after the crosslinking treatment was immersed for 10 seconds in a second crosslinking bath at 40° C. containing potassium iodide / boric acid / pure water (mass ratio) of 9 / 2.9 / 100.

[0127] (5) Cleaning process Next, the film after the second crosslinking treatment was immersed in a cleaning bath containing pure water at 14°C for 5 seconds, and the shower volume was 5 m 3 / h and shower temperature 14°C.

[0128] (6) Drying process Next, the film after the washing process was passed through a drying oven and heated and dried at 80°C for 190 seconds to produce a polarizer film. The moisture content after drying was 13.6%, and the thickness of the obtained polarizer film was about 21 μm.

[0129] (7) Bonding process Next, a water-based adhesive containing 5 parts by weight of polyvinyl alcohol per 100 parts by weight of water was prepared as an adhesive. Then, protective films were laminated on both sides of the polarizer film using the prepared UV adhesive. The obtained laminate was exposed to UV light to harden the adhesive, and an upper polarizing plate and a lower polarizing plate were produced. The thickness of the adhesive layer in the obtained polarizing plate was about 2 μm.

[0130] Production Example 2: Production of composition for forming hard coating layer A composition for forming a hard coating layer was prepared by mixing 16.2 g of a dendrimer compound (Miwan Specialty Chemical, SP-1106), 14.4 g of inorganic nanoparticles (10 to 20 nm, silica particles: 50 wt %, solvent: methyl ethyl ketone (MEK)), 1.8 g of a multifunctional (meth)acrylate compound containing an ethylene glycol group, 0.7 g of a photoinitiator (1-hydroxycyclohexylphenyl ketone), and 2.9 g of methyl ethyl ketone.

[0131] Manufacturing Example 3: Production of hard coating layer The composition for forming the hard coating layer prepared in Preparation Example 2 was applied to one side of each of the upper and lower polarizing plates prepared in Preparation Example 1, adjusted in type and solid content to a Mayer Bar, cured, and then coated with a Bar at a calculated hard coating thickness. The hard coating was then dried at 80° C. for 5 minutes and then heated with a high-pressure mercury lamp at 500 mJ / m 2 The hard coating layer was formed on one surface of each of the upper and lower polarizing plates.

[0132] Manufacturing Example 4: Fabrication of transparent conductive layer The upper and lower polarizing plates manufactured in Preparation Example 1 or 3 were inserted, 450 W DC power was applied to operate the sputtering gun, and plasma was then induced to the ITO (10 wt% Sn doped In2O3) target to form a transparent conductive film (90 nm). The formed transparent conductive film was ion-treated by operating an ion gun with 50 W DC power. At this time, the pressure was maintained at 3 mTorr at room temperature, and argon gas and oxygen gas were supplied at 30 sccm and 1 sccm, respectively. At this time, the ITO thickness was measured by FT-SEM, and the ITO sheet resistance (m 2 / □) was measured using a four point probe.

[0133] Manufacturing Example 5: Fabrication of Alignment Film An alignment liquid was coated on the ITO surfaces of the upper and lower polarizers prepared in Preparation Example 4 and dried (80° C. / 2 min.), and then UV was irradiated onto the dried alignment liquid to prepare an alignment film.

[0134] Manufacturing Example 6: Spacer Scattering Manufacturing First, 0.03 g of ball spacers (SP-210 by SEKISUI) was mixed with 100 ml of IPA to prepare a mixed solvent. Then, the conductive layer laminate of the lower polarizer of Preparation Example 5 was placed in a spacer sprayer (SDSS-KHU02, SHINDO ENG LAB) and the mixed solvent prepared above was sprayed at 110° C. and dried for 20 minutes to form ball spacers on the alignment film of the lower polarizer.

[0135] Manufacturing Example 7: Production of optical laminate A sealant (UVF-006, 70,000 mPa s, Sekisui) was applied to the outer periphery of the lower polarizing plate manufactured in Manufacturing Example 6 using a sealant dispenser (SHOT mini 200Ωx, Musashi) according to the product size. Then, with the polarization axes of the upper and lower polarizing plates arranged parallel to each other at 0° or 90°, liquid crystal was injected onto the alignment film of the upper polarizing plate using the ODF process to bond the upper and lower polarizing plates. Then, UV curing (500 mJ / cm) was performed along the sealant line. 2 ) was carried out to produce an optical laminate for smart windows.

[0136] Examples and Comparative Examples Example 1 An optical laminate of Example 1 was manufactured in which the upper hard coating layer of the upper polarizer had a thickness of 2 μm and the lower hard coating layer of the lower polarizer had a thickness of 2 μm according to Preparation Examples 1 to 7. The outer and inner protective films of the upper polarizer were TAC films having a thickness of 60 μm and 40 μm, respectively, and the outer and inner protective films of the lower polarizer were TAC films having a thickness of 40 μm, respectively.

[0137] Example 2 An optical laminate of Example 2 was prepared in which the upper hard coating layer of the upper polarizer had a thickness of 5 μm and the lower hard coating layer of the lower polarizer had a thickness of 5 μm, according to Preparation Examples 1 to 7. The outer and inner protective films of the upper polarizer were TAC films having a thickness of 60 μm and 40 μm, respectively, and the outer and inner protective films of the lower polarizer were TAC films having a thickness of 40 μm, respectively.

[0138] Example 3 An optical laminate of Example 3 was prepared in which the upper hard coating layer of the upper polarizer had a thickness of 20 μm and the lower hard coating layer of the lower polarizer had a thickness of 20 μm, according to Preparation Examples 1 to 7. The outer and inner protective films of the upper polarizer were TAC films having a thickness of 60 μm and 40 μm, respectively, and the outer and inner protective films of the lower polarizer were TAC films having a thickness of 40 μm, respectively.

[0139] Example 4 An optical laminate of Example 4 was manufactured in which the upper hard coating layer of the upper polarizer had a thickness of 2 μm and the lower hard coating layer of the lower polarizer had a thickness of 2 μm, according to Preparation Examples 1 to 7. The outer and inner protective films of the upper polarizer were a TAC film having a thickness of 60 μm and a COP film having a thickness of 50 μm, respectively, and the outer and inner protective films of the lower polarizer were a TAC film having a thickness of 40 μm and a COP film having a thickness of 50 μm, respectively.

[0140] Example 5 An optical laminate of Example 5 was manufactured in which the upper hard coating layer of the upper polarizer had a thickness of 5 μm and the lower hard coating layer of the lower polarizer had a thickness of 5 μm, according to Preparation Examples 1 to 7. The outer and inner protective films of the upper polarizer were a TAC film having a thickness of 60 μm and a COP film having a thickness of 50 μm, respectively, and the outer and inner protective films of the lower polarizer were a TAC film having a thickness of 40 μm and a COP film having a thickness of 50 μm, respectively.

[0141] Example 6 An optical laminate of Example 6 was manufactured in which the upper hard coating layer of the upper polarizer had a thickness of 20 μm and the lower hard coating layer of the lower polarizer had a thickness of 20 μm, according to Preparation Examples 1 to 7. The outer and inner protective films of the upper polarizer were a TAC film having a thickness of 60 μm and a COP film having a thickness of 50 μm, respectively, and the outer and inner protective films of the lower polarizer were a TAC film having a thickness of 40 μm and a COP film having a thickness of 50 μm, respectively.

[0142] Comparative Example 1 According to Preparation Examples 1 to 7, an optical laminate of Comparative Example 1 was prepared in which an upper hard coating layer having a thickness of 14 μm was provided only on one side of an upper polarizer. The outer and inner protective films of the upper polarizer were a TAC film having a thickness of 60 μm and a TAC film having a thickness of 40 μm, respectively, and the outer and inner protective films of the lower polarizer were a TAC film having a thickness of 40 μm and a COP film having a thickness of 50 μm, respectively.

[0143] Comparative Example 2 An optical laminate of Comparative Example 2 in which the upper polarizer and the lower polarizer did not include a hard coating layer was manufactured by Preparation Examples 1 and 4 to 7. At this time, the outer and inner protective films of the upper polarizer were a TAC film having a thickness of 80 μm and a COP film having a thickness of 50 μm, respectively, and the outer and inner protective films of the lower polarizer were a TAC film having a thickness of 80 μm and a COP film having a thickness of 50 μm, respectively.

[0144] Comparative Example 3 An optical laminate of Comparative Example 3 in which the upper polarizer and the lower polarizer did not include a hard coating layer was manufactured by the same methods as Preparation Examples 1 and 4 to 7, except that a thermosetting alignment film was used for the preparation of the alignment film and the curing conditions were 110°C, 30 minutes. At this time, the outer and inner protective films of the upper polarizer were a TAC film having a thickness of 60 μm and a COP film having a thickness of 50 μm, respectively, and the outer and inner protective films of the lower polarizer were a TAC film having a thickness of 40 μm and a COP film having a thickness of 50 μm, respectively.

[0145] Experimental Example (1) Evaluation of pencil hardness For the optical laminates of Examples 1 to 6 and Comparative Examples 1 to 3, a pencil hardness tester (manufactured by SUKBO Chemical Co., Ltd., Korea) was used to measure the pencil hardness of the hard coating layer surface of the polarizing plate (or the inner surface of the polarizing plate) under a load of 500 g, and the results are shown in Tables 1 and 2. A Mitsubishi pencil was used, and the pencil hardness was measured based on whether scratches were generated after five tests per pencil hardness and heat treatment at 100° C. for 10 minutes.

[0146] (2) Evaluation of reliability of mandrels In order to evaluate the bending properties and cracking properties of the optical laminates of Examples 1 to 6 and Comparative Examples 1 to 3 using a cylindrical bending tester (Lab-Q D605, manufactured by CKSI), sample specimens of the Examples and Comparative Examples, each having a size of 100 x 100 mm, were placed so that the lower polarizing plate was in contact with an iron bar having a diameter of 4 mm, and in a folded state, a load of 1 kg was applied to the outside of the folded area, and the sample was placed in an oven at 90°C for 2 hours. The sample was then placed at room temperature and the folded area was observed to evaluate the occurrence of cracks, and the results are shown in Tables 1 and 2 below. <Evaluation criteria> Good: No cracks Defective: One or more cracks occur.

[0147] (3) Steel wool test The optical laminates of Examples 1 to 6 and Comparative Examples 1 to 3 were subjected to 10 reciprocating motions at a speed of 100 mm / sec under 1 kg / (2 cm x 2 cm) using a steel wool tester (WT-LCM100, manufactured by Protec, Korea) to evaluate the abrasion resistance of the polarizing plate hard coating layer surface, and the results are shown in the following Tables 1 and 2. #0000 steel wool was used. <Evaluation criteria> ○: No scratches or discoloration △: 1 to 10 scratches and no discoloration ×: More than 10 scratches and discoloration

[0148] [Table 1]

[0149] [Table 2]

[0150] Referring to Tables 1 and 2, in the case of the optical laminates of Examples 1 to 6 in which the pencil hardness of the upper and lower hard coating layers is 3B to 6H, respectively, the reliability mandrel evaluation results show that no cracks are generated, the steel wool test results show that there are no or less than 10 scratches, and no discoloration occurs.

[0151] In particular, the optical laminates of Examples 2, 3, 5 and 6, in which the pencil hardness of the upper and lower hard coating layers is HB to 6H, respectively, show better reliability mandrel evaluation results and steel wool test results than the optical laminates of Examples 1 and 4.

[0152] Meanwhile, in the case of the optical laminates of Comparative Example 1 in which a hard coating layer is provided only on the upper polarizer, and Comparative Examples 2 and 3 in which a hard coating layer is not provided, the reliability mandrel evaluation results and steel wool test results were poor compared to the examples.

[0153] Therefore, when two different polarizing plates included in the optical laminate each include a functional layer, i.e., a hard coating layer, and the surface pencil hardness of the hard coating layer is 3B to 6H, more preferably HB to 6H, it can be seen that not only is the abrasion resistance excellent, but the bending resistance and durability are further improved. [Industrial Applicability]

[0154] According to the variable transmittance optical laminate of the present invention, the process of forming a conductive layer on a substrate and then bonding it to other components required for forming a conventional optical laminate can be omitted, and the manufacturing process can be simplified compared to the conventional optical laminate.

Claims

1. a first polarizing plate including a first functional layer; a first transparent conductive layer formed on one surface of the first polarizing plate; a second polarizing plate including a second functional layer and facing the first polarizing plate; a second transparent conductive layer formed on one surface of the second polarizing plate and facing the first transparent conductive layer; a liquid crystal layer provided between the first transparent conductive layer and the second transparent conductive layer; At least one of the first transparent conductive layer and the second transparent conductive layer is formed in direct contact with one of the first polarizing plate and the second polarizing plate, The variable transmittance optical laminate, wherein the first functional layer and the second functional layer have a surface pencil hardness of 3B to 6H.

2. The variable transmittance optical laminate according to claim 1 , wherein the first functional layer and the second functional layer have a surface pencil hardness of HB to 6H.

3. The variable transmittance optical laminate according to claim 1 , wherein the first functional layer and the second functional layer include at least one of a hard coating layer and a low refractive index layer.

4. The low refractive index layer is made of SiO 2 , Al 2 O 3 , MgF 2 , CaF 2 4. The variable transmittance optical laminate according to claim 3, comprising at least one selected from the group consisting of fluorine, fluorine, fluorine-containing silica, fluorine-containing fluorine, and cryolite.

5. 2. The variable transmittance optical laminate of claim 1, wherein at least one of the first transparent conductive layer and the second transparent conductive layer is formed in direct contact with one of the first polarizer and the second polarizer without a separate substrate between the transparent conductive layer and the first polarizer and the second polarizer.

6. 2. The variable transmittance optical laminate of claim 1, wherein at least one of the first transparent conductive layer and the second transparent conductive layer includes an easy-adhesion layer between the first polarizing plate and the second polarizing plate and is formed in direct contact with the first polarizing plate and the second polarizing plate.

7. 2. The variable transmittance optical laminate of claim 1, wherein at least one of the first transparent conductive layer and the second transparent conductive layer comprises at least one selected from the group consisting of transparent conductive oxides, metals, carbon-based materials, conductive polymers, conductive inks, and nanowires.

8. 2. The variable transmittance optical laminate according to claim 1, wherein at least one of the first polarizing plate and the second polarizing plate further comprises at least one selected from the group consisting of a protective layer, a phase difference control layer, and a refractive index control layer.

9. The variable transmittance optical laminate of claim 1 , wherein at least one of the first polarizing plate and the second polarizing plate has a thickness of 30 to 200 μm.

10. The variable transmittance optical laminate according to claim 1, wherein the liquid crystal layer includes at least one spacer selected from the group consisting of a ball spacer and a column spacer.

11. 11. The variable transmittance optical stack of claim 10, wherein the spacers have a diameter of 1 to 10 μm.

12. The variable transmittance optical laminate according to claim 10, wherein the area of ​​the spacer in the liquid crystal layer is 0.01% to 10% of the area of ​​the liquid crystal layer.

13. The variable transmittance optical laminate according to claim 1 , further comprising at least one layer selected from the group consisting of an alignment film, an adhesive layer, and an ultraviolet absorbing layer.

14. A method for producing the variable transmittance optical laminate according to any one of claims 1 to 13.

15. A smart window comprising the variable transmittance optical laminate of any one of claims 1 to 13.

16. A means of transportation comprising the smart window of claim 15.

17. 16. A car comprising the smart window according to claim 15, applied to at least one of a front window, a rear window, a side window, a sunloop window, and an interior partition.

18. A wearable device comprising the smart window of claim 15.

19. Architectural fittings comprising the smart window of claim 15.